Molecular Evolution of Extensively Drug-Resistant (XDR) Pseudomonas aeruginosa Strains From Patients and Hospital Environment in a Prolonged Outbreak - Buhl, Michael; Kästle, Christina; Geyer, André; Autenrieth, Ingo B.; Peter, Silke; Willmann, Matthias (Frontiers in Microbiology, 2019)
In this study, we aimed at elucidation of a prolonged outbreak of extensively drug-resistant (XDR) Pseudomonas aeruginosa, going on at two adjacent hospitals over a time period of four years. Since all strains exhibited a similar antibiotic susceptibility pattern and carried the carbapenemase gene blaVIM, we assumed a monoclonal outbreak. To shed light on the intra-hospital evolution of these strains over time, whole genome sequence (WGS) analysis of 100 clinical and environmental outbreak strains was employed. Phylogenetic analysis of the core genome revealed the outbreak to be polyclonal, rather than monoclonal as initially suggested. The vast majority of strains fell into one of two major clusters, composed of 27 and 59 strains, and their accessory genome each revealed over 400 and 600 accessory genes, respectively, thus indicating an unexpectedly high structural diversity among phylogenetically clustered strains. Our investigation clearly shows both accumulation and loss of genes to occur very frequently over time, as reflected by analysis of protein enrichment as well as functional enrichment. In addition, we investigated adaptation through single nucleotide polymorphisms (SNPs). Among the genes affected by SNPs, there are a multidrug efflux pump (mexZ) and a mercury detoxification operon (merR) with deleterious mutations potentially leading to loss of repression with resistance against antibiotics and disinfectants. Our results not only confirm WGS to be a powerful tool for epidemiologic analyses, but also provide insights into molecular evolution during an XDR P. aeruginosa hospital outbreak. Genome mutation as well as genomic rearrangements unveiled a striking genetic plasticity on an unexpectedly high level, mostly driven by horizontal gene transfer. Our study adds valuable information to the molecular understanding of ‘real-world’ in-hospital P. aeruginosa evolution and is a step forward to a more personalized medicine in infection control.